Gamification: Strategy to Pull the Intention of DKI Jakarta Residents (Choice User) to Use Public Transportation - Dian Siskawati; Puspita Dirgahayani (Faculty of Engineering, Andi Djemma University, 2024)
The higher practice of private car use in DKI Jakarta amid the implementation of the TDM strategy that continues to be developed leads to increased traffic congestion, which in turn causes economic losses, deteriorated air quality, and an increase in acute respiratory tract infection cases. Innovation is needed in the pull strategy of DKI Jakarta residents to suppress this behavior, especially those who have (access to) private vehicles to switch to public transportation. This study tries to analyze the effect of gamification on the behavioral intentions of DKI Jakarta residents (choice users) to use public transit for their daily activities (school/college/work). Modifications to the Theory of Planned Behavior (TPB) were carried out to investigate the influence of gamification through attitudes and behavioral control on behavioral intentions to use public transportation. The theory was tested using questionnaire data from 200 respondents with SEM-PLS analysis. The elements of points, levels, rewards, and games are used as indicators of gamification. This study shows that gamification positively and significantly affects attitudes and behavioral control. The study findings confirm the significant positive influence of attitudes on behavioral intentions to use public transportation. The results of this research can also be used as material for consideration in pull strategy (TDM) policy innovation in DKI Jakarta.